An advanced system for portfolio optimisation. (1st January 2014) - Beraldi, Patrizia; Grandinetti, Lucio; Epicoco, Italo; Violi, Antonio; Bruni, Maria Elena
Portfolio optimisation is a crucial problem that every financial operator has to deal with. Nowadays the possibility to process large amount of data, to generate more confident forecasts and to solve more complex optimisation problems is powered by the adoption of advanced computing systems. This paper presents an efficient and effective decision support system for portfolio optimisation implemented on a grid platform. The system relies on a methodological kernel which efficiently integrates simulation and optimisation techniques. A large set of numerical experiments has been carried out to measure the performance of the system both in terms of computational efficiency and improved solution quality.